Analisis Rasio Keuangan Sebagai Alat Untuk Mengukur Kinerja Perusahaan PT. Telkom Indonesia (Persero) Tbk Periode Tahun 2016-2020 - Lela Khusnul Pratiwi; Novi Khoiriawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to measure the performance of PT. Telkom Indonesia (Persero) as seen from the liquidity ratio, profitability ratio, solvency ratio, and asset ratio. To measure performance at PT. Telkom Indonesia (Persero) Tbk in 2016-2020 analytical tools used liquidity ratios, profitability ratios, solvency ratios and activity ratios and compare them with the industry average ratio which includes PT. Indosat Tbk, PT Xl Axiata Tbk, and PT Smartfreen Telcom Tbk. The liquidity ratio using the current ratio shows that liquidity is above the industry average. The profitability ratio using return on assets shows that the financial performance of PT. Telkom Indonesia (Persero) is higher than the industry average. The solvency ratio using the debt to equity ratio shows that the solvency of PT. Telkom Indonesia (Persero) Tbk is below the industry average. The activity ratio using total assets turn over shows that PT. Telkom Indonesia (Persero) Tbk has a turnover that is faster than the industry average. Overall the financial performance of PT. Telkom Indonesia (Persero) Tbk is higher than the industry average. Keywords : Liquidity,Profitability,Solvency,Activity, company performance